Effect Of Bangun-Bangun Leaves Ethanol Extract On Lipid Profile Ovariectomized Female Rats - Suharyanisa; Hasibuan, Poppy Anjelisa Zaitun; Nasution, Pandapotan (Talenta Publisher, 2021)
Menopause was a condition of the body when ovaries stopped producing ovum; ovum is the main producer of estrogen hormone. Menopause can increasing lipid profile in blood; it causes any problems in the cardiovascular system. People of North Sumatra have long used Bangun-Bangun leaves as a breastfeeding agent; it contains flavonoid bioactive compounds, which are be expected to replace lost estrogen hormone. This study determined the estrogenic activity of Bangun-Bangun leaves ethanol extract (BBLEE) on lipid levels of ovariectomized female rats as a menopausal model. BBLEE has obtained by maceration techniques with 96% ethanol and extract used on 24 ovariectomized rats which were divided into 6 groups. Group 1 (normal), group 2 (positive) was treated by estradiol at dose of 0.18 mg/kg BW, group 3 (negative) was treated by 0.5% Na-CMC and group 4, 5, 6 were treated by BBLEE at dose of 30, 60, 90 mg/kg BW given orally for 14 days. The data were analyzed by ANOVA and Post Hoc Tukey HSD test. The result showed that effective dose of BBLEE was 90 mg/kg BW which improved lipid profile (TC = 55.75±0.47; TG = 63.00±0.40; HDL = 37.00±0.81; LDL = 30.50±0.86) in blood of ovariectomized female rats as a menopausal model. BBLEE at the dose of 90 mg/kg BW can ameliorate the lipid profile in the blood of ovariectomized female rats as a menopausal model.